Profile of Pediatric Nephrotic Syndrome in Wahidin Sudirohusodo Hospital, Makassar, Indonesia - Husein Albar; Fadel Bilondatu (Cermin Dunia Kedokteran, 2019)
Introduction: Nephrotic syndrome is a common and important pediatric chronic renal disease, characterized by massive proteinuria, hypoalbuminemia, edema and hypercholesterolemia. This study was to assess the profile of pediatric nephrotic syndrome at Wahidin Sudirohusodo Hospital Makassar over a 7-year period. Methods: A retrospective study on hospitalized nephrotic syndrome patients at pediatric nephrology ward in Wahidin Sudirohusodo Hospital Makassar from January 2011 to December 2017. Demographic, clinical and laboratory data were extracted from medical records. Results: A total of 142 children with nephrotic syndrome who fulfilled the inclusion criteria was analyzed. Age at onset ranged from 1.4 to 17.5 years (mean 8.5 years), the majority (66.2%) was 5 year-old and above, predominantly boy (66.2%) with a boy to girl ratio of 1,95:1 and well-nourished (56.3%). Upper respiratory infections were observed in 36.6% cases. The predominant clinical signs and symptoms were edema (100%), hypertension (26.8%). Patients with relapse were 56.3%, and the mortality was 2.12%. The prevalent laboratory findings were microscopic hematuria (50.7%), massive proteinuria (100%), hypoalbuminemia (100%), hypercholesterolemia (100%), and elevated serum creatinine (9.9%). Conclusion: The profile of pediatric nephrotic syndrome at Wahidin Sudirohusodo Hospital Makassar was similar to typical children nephrotic syndrome and did not significantly differ from other studies.Introduksi : Sindrom nefrotik adalah penyakit kronis anak yang sering dan penting di seluruh dunia, ditandai oleh proteinuria masif, hipoalbuminemia, edema dan hiperkolesterolemia. Studi ini untuk menentukan profil sindrom nefrotik anak di rumah sakit Wahidin Sudirohusodo Makassar. Metode : Penelitian retrospektif 7 tahun pada pasien sindrom nefrotik di bangsal nefrologi anak rumah sakit Wahidin Sudirohusodo Makassar dari bulan Januari 2011 sampaidengan Desember 2017. Data diambil dari rekam medik terdiri dari data demografi dan temuan klinis dan laboratorium. Hasil: Total 142 pasien sindrom nefrotik anak yang memenuhi kriteira inklusi dianalisis. Umur pasien saat onset mulai dari 1,4 sampai dengan 17,5 tahun dengan rerata umur 8,5 tahun. Kebanyakan berumur 5 tahun atau lebih (66.2%) didominasi pasien laki-laki (66,2%) dengan rasio jenis kelamin 1,95:1. Status gizi baik (56,3%). Infeksi saluran napas atas ditemukan pada 36,6% kasus. Gejala dan tanda klinis utama adalah edema (100%), hipertensi (26,8%), Relaps pada 56,3% kasus dan 2,12% pasien meninggal. Temuan laboratorium utama adalah hematuria mikroskopik (50,7%), proteinuria masif (100%), hipoalbuminemia (100%), hiperkolesterolemia (100%), dan peningkatan kreatinin serum (9,9%). Simpulan: Profil sindrom nefrotik anak di rumah sakit Wahidin Sudirohusodo Makassar pada umumnya serupa dan tidak berbeda bermakna dari penelitian lain.